A imagem da palavra na obra de Raul Córdula - Azevedo, Sidney Leonardo Albuquerque de (2013)
This research discusses the creative processes of the visual artist and art critic Raul Córdula Filho, from Paraiba, in the treatment which he gives to the word as a visual image impregnated with memories, political positions and incursions into his private imaginary, as well as collective symbolic references, where issues of art-and-life are discussed in the panorama of contemporary visual culture, merging the universe of writing with the visual arts. The investigation is founded in the production of the esthetic-subject, focused in a critical genetic approach that occurs in the inset of intersemiotic speech, considering the appropriation of the word as a reframing of its lexical power, synergic point of multiple open plurilateral readings. This dissertation intends to point out and discuss the conceptions and enunciative practices of the artist, sedimented in the peculiar exercise of the power to verbalize and shape his ideas through the syntactic elements of orality enrolled in the supports and expressive categories established in the universe of the visual arts, thus conferring to the word the re-presentation of intertextual and intersemiotic meanings.